THE EFFECT OF MACROECONOMIC VARIABLES ON THE PRICE OF SHARIA HEALTH SECTOR SHARES LISTED ON THE JAKARTA ISLAMIC INDEX 70 (JII70) FOR THE PERIOD 2018-2022 - Indah Lestari Anwar; Retno Fitrianti; Sukmatica Slamet; Armin Amri; Aulia Rahman (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study examines the impact of macroeconomic factors on the performance of health sector sharia stocks listed on the Jakarta Islamic Index 70 (JII 70). The research adopts a quantitative approach, utilizing panel data regression to analyze the relationship between inflation, exchange rates, and the share prices of health sector issuers included in the JII 70. This research falls under the category of quantitative descriptive analytics. The population of this study consists of all health sector issuers listed on the JII 70 Islamic stock index. The sample includes health sector issuers registered on the JII 70 Islamic stock index from 2018 to 2022. The findings reveal that inflation has no significant impact on health sector Islamic stocks. Furthermore, the results indicate a negative correlation between exchange rates and stock prices, although this relationship is not statistically significant. Overall, the macroeconomic variables examined, namely inflation and exchange rates, do not exert a significant influence on the value of Islamic equities in the healthcare sector. Nevertheless, investors should still monitor these indicators as economic conditions can change unpredictably.